Molecular Structure and Reactivity of the Group V Metal Oxides - Wachs, Israel E. (2000)
The molecular structures and reactivity of the group V metal oxides (V2O5, Nb2O5 and Ta2O5) were compared. Their solid state structural chemistry, physical and electronic properties, number of active surface sites and their chemical reactivity properties were examined. For the bulk oxides, the solid state structural chemistry and the physical and electronic properties are well established. The number of active surface sites and the distribution of surface redox/acid sites were determined with methanol chemisorption and methanol oxidation, respectively. These studies revealed that the active surface sites present in pure V2O5 are primarily redox sites and the active surface sites in pure Nb2O5 are essentially acidic in nature. Furthermore, the surface redox sites present in pure V2O5 are orders of magnitude more active than the surface acid sites in pure Nb2O5. Consequently, the catalytic properties of bulk V2O5-Nb2O5 mixed oxides are dominated by the vanadia component. For the supported metal oxides, where the group V metal oxides are present as two-dimensional metal oxide overlayers, the structural and electronic properties are not well established in the literature. From a combination of molecular spectroscopic characterization methods (e.g., XANES, Raman, IR and UV-Vis DRS), it was possible to obtain this fundamental information. Methanol chemisorption studies demonstrated that a similar number of active surface sites are present in the supported vanadia and niobia catalyst systems. Similar to their bulk oxides, the surface vanadia species possess redox characteristics and the surface niobia species primarily possess acidic characteristics (Lewis acidity). The surface niobia species was a very sluggish redox site during oxidation reactions (e.g., methanol oxidation to formaldehyde and SO2 oxidation to SO3), but significantly promoted the surface vanadia redox sites for oxidation reactions that required dual surface redox and acid sites (e.g., butane oxidation to maleic anhydride and selective catalytic reduction of NOx by NH3 to produce N2). These new fundamental insights are allowing for the molecular engineering of group V metal oxide catalysts (especially vanadia and niobia). In contrast, the molecular structure and reactivity properties of Ta2O5 catalysts are not yet established and will require significant research efforts. © 2000 Elsevier Science B.V All rights reserved.